2017
DOI: 10.4103/ayu.ayu_18_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antidiabetic potential of partially purified bioactive fractions from four medicinal plants in alloxan-induced diabetic rats

Abstract: Background:Syzygium cumini, Terminalia chebula, Trigonella foenum graecum and Salvadora persica are medicinally important plants well known for their pharmacological activities.Aim:The aim of this study is to compare the antidiabetic potential of partially purified bioactive fractions isolated from four targeted medicinal plants in diabetic rats.Methods:Alloxan was administered (125 mg/kg, IP) in albino Wistar rats to produce diabetes. The partially purified bioactive fractions, namely S. cumini tannin fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Another study carried out in an experimental model of DM2, induced by treatment with alloxan, a diabetogenic chemical agent (Awar et al, 2016), showed that treatment with Syzygium cumini seed extract promoted antidiabetic activities and antihyperglycemic effect, showing is a potent and safe ally for the treatment of T2DM (Bansode et al, 2017). Similar to what was previously observed in an in vitro study with L6 myogenic cells, where Syzygium cumini promoted increased expression of phosphoinositide 3 (PI3) kinase, an essential enzyme in insulin signaling.…”
Section: Syzygium Cumini Lsupporting
confidence: 70%
“…Another study carried out in an experimental model of DM2, induced by treatment with alloxan, a diabetogenic chemical agent (Awar et al, 2016), showed that treatment with Syzygium cumini seed extract promoted antidiabetic activities and antihyperglycemic effect, showing is a potent and safe ally for the treatment of T2DM (Bansode et al, 2017). Similar to what was previously observed in an in vitro study with L6 myogenic cells, where Syzygium cumini promoted increased expression of phosphoinositide 3 (PI3) kinase, an essential enzyme in insulin signaling.…”
Section: Syzygium Cumini Lsupporting
confidence: 70%
“…Several studies reported that alloxan is a non-ideal diabetogenic agent [ 14 , 15 ]. However, many studies have successfully used this agent [ 31 , 32 ]. Various antidiabetic candidates were assessed using alloxan-induced diabetic rats [ 29 , [33] , [34] , [35] ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute in-vivo studies of ethanol extract (100 mg/kg p.o.) of Syzygium cumini seeds in alloxan-induced diabetic rats showed a decrease in serum glucose level by 88mg/dl as compared to Gibenclamide (97mg/dl) (Bansode et al, 2017). In another study, in-vivo antidiabetic activity of chloroform, methanol and aqueous extracts of Syzygium cumini seeds were assessed histologically in streptozotocin (STZ) induced diabetic mice and the results revealed restoration of normoglycemia, increase in G6PD, Plasma insulin and C-Peptide levels in the chloroform extract (Dusane and Joshi, 2011).…”
Section: Antidiabetic Activitymentioning
confidence: 94%